Implementasi Penerapan Protokol New Normal Pada Destinasi Wisata Di Kabupaten Sleman - Saputra, Arif Dwi (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2021)
This research was conducted to determine the implementation of the new standard protocol for tourist destinations in Sleman Regency, to check the actual conditions of the readiness of tourist destinations to reopen and to see the compliance of tourists to the regulations of the new standard protocol in Sleman Regency. The research method uses quantitative-based data with a survey method. The research location took eight leading tourist destinations in Sleman Regency, namely: Monjali, Prambanan Temple, Blue Lagoon, Deswita Pentingsari, Deswita Kelor, Sleman City Hall, Abhayagiri, and Hotel Sahid Jaya. They were collecting data using field observations, questionnaires, and literature studies. The research was carried out on 1-24 August 2020. The results showed that the tourism sector in Sleman Regency could be reopened with various conditions for the good of all parties, significantly improving the community's economy. The opening of tourist destinations in Sleman Regency must be accompanied by strict supervision, especially regarding implementing health protocols